"I think everyone's been thrilled": Music teachers' perspectives on school music performance collaborations. (August 2017) - Sutherland, Andrew Thomas
Thanks to the efforts of music teachers in arranging concerts, young musicians develop a multitude of skills when performing with others. Music teachers are notoriously time-poor with the pressures of various curricular and co-curricular demands. To find time to provide performance opportunities for students that involve other schools adds layers of administrative complexities to an already comprehensive workload. Although there is literature to suggest the benefits of collaboration, the necessities of getting the mechanics of a music department running smoothly often places the idea of musical collaboration in the category of "luxury" to be considered "when there is time". The experiences of several music teachers from different schools who have collaborated on a series of concerts performed biannually evolved over six years and significantly impacted their music departments. An important component of these concerts was the impact of the visiting conductors who acted as "Artists in Residence" in the lead up to the performance. The findings suggest collaboration as being vital to the building process of a developing Music Department and the article makes recommendations for the use of guest conductors.